The last of the Mohicans (Leatherstocking tales, 2, 1, 1919)
"James Fenimore Cooper's romantic adventure brings the wilds of the American frontier and the drama of the French-Indian War vividly to life. The most popular of Cooper's Leatherstocking Tales, The Last of the Mohicans portrays the inevitable conflict of opposed cultures and stands as a testament to the ways in which this struggle has been mythologized. Featuring the well-loved noble woodsman Natty Bumppo, or "Hawk-eye," Cooper's novel is a memorable depiction of courage and passion, and a precursor to the Western genre."--BOOK JACKET.
The world of James Fenimore Cooper and The last of the Mohicans , Introduction by Stephen Railton , Cooper's introduction , The last of the Mohicans , Endnotes , Inspired by The last of the Mohicans , Comments & questions , For further reading.

Barnaby Rudge: a domestic drama in three acts (Dicks' standard plays, no. 393,, 1883)
Description Not Provided

Little women (Little Women series, 1, 1, 2012)
For generations, children around the world have come of age with Louisa May Alcott's March girls: hardworking eldest sister Meg, headstrong, impulsive Jo, timid Beth, and precocious Amy. With their father away at war, and their loving mother Marmee working to support the family, the four sisters have to rely on one another for support as they endure the hardships of wartime and poverty. We witness the sisters growing up and figuring out what role each wants to play in the world, and, along the way, join them on countless unforgettable adventures. Readers young and old will fall in love with this beloved classic, at once a lively portrait of nineteenth-century family life and a feminist novel about young women defying society's expectations.
Four sisters , A merry Christmas , The Laurence boy , Being neighborly , Jo and her temper , Meg tries to be fashionable , Summer and dreams , Secrets , A telegram , Dark days , Serious conversations , Aunt March settles the question , The first wedding , Endeavors , Domestic experiences , Calls , Jo's friend , Heartache , Beth's secret , Lazy Laurence , The Valley of the Shadow , Learning to forget , All alone , Under the umbrella.

Martin Eden (Penguin American library, ,, 2019)
Recounts the story of Martin Eden, a young seaman struggling to obtain social and intellectual recognition as a writer.

The day of the confederacy: a chronicle of the embattled South (Chronicles of America, 30,, 1919)
Description Not Provided

The adventures of Huckleberry Finn (Classic collection), ,, 2011)
Called "the veriest trash" by a member of the Concord, Massachusetts Library Board that banned the novel when it was first published, Huckleberry Finn has come to be viewed, as H.L. Mencken put it, as "one of the great masterpieces of the world." Ernest Hemingway wrote that "All modern American literature comes from one book by Mark Twain called Huckleberry Finn....There was nothing before. There has been nothing as good since." A daringly ironic attack on racism American-style, Twain's story of what he once called a "sound heart" triumphing over a "deformed conscience" is poignant, powerful, and fresh. It is no wonder that this extraordinary book continues to captivate readers around the world. This handsome Oxford World's Classic edition uses the reliable 1885 text and includes in-depth, up-to-date editorial apparatus
Discover Moses and the bulrushers , Our gang's dark oath , We ambuscade the A-rabs , Hair-ball oracle , Pap starts in on a new life , Pap struggles with the Death Angel , I fool Pap and get away , I spare Miss Watson's Jim , House of death floats by , What comes of handlin snake-skin? , They're after us! , "Better let blame well alone" , Honest loot from the "Walter Scott" , Was Solomon wise? , Fooling poor old Jim , Rattlesnake-skin does its work , Grangerfords take me in , Why Harney rode away for his hat , Duke and the Dauphin come aboard , What royalty did to Parkville , Arkansaw difficulty , Why the lynching bee failed , Orneriness of kings , King turns parson , All full of tears and flapdoodle , I steal the king's plunder , Dead Peter has his gold , Overreaching don't pay , I light out in the storm , Gold saves the thieves , You can't pray a lie , I have a new name , Pitiful ending of royalty , We cheer up Jim , Dark, deep-laid plans , Trying to help Jim , Jim gets his witch pie , "Here a captive heart busted" , Tom writes nonnamous letters , Mixed-up and splendid rescue , "Must 'a' been sperits" , Why the didn't hang Jim , Last. Nothing more to write.

The Five civilized tribes (The Civilization of the American Indian, ,, 1934)
Description Not Provided

Uncle Tom's cabin : or, Life among the lowly (Penguin American library, ,, 1995)
The moving abolitionist novel that fueled the fire of the human rights debate in 1852 and melodramatically condemned the institution of slavery through such powerfully realized characters as Tom, Eliza, Topsy, Eva, and Simon Legree. First published more than 150 years ago, this monumental work is today being reexamined by critics, scholars, and students.

Buffalo Bill (The American adventure, ,, 1943)
Buffalo Bill, went from a buffalo hunter to become the owner of a "Wild West Show."
A man's job , The young trappers , Boys of the pony , Wagon trains, stagecoaches, and railroads , Buffalo Bill, army scout.

The Navajo and Pueblo silversmiths (Civilization of the American Indian, ,, 2015)
The story of the Indian silver jewelry fashioned in the Southwest by the Navajo, Zuni, Hopi, and other Pueblo peoples by John Adair, a recognized expert on this craft.

Buffalo Bill: boy of the Plains (Childhood of famous Americans, ,, 1948)
Description Not Provided

Moby-Dick (Graphic classics (Magic Wagon), , 1, 1990)
"Herman Melville's Moby-Dick is considered by many readers to be the Great American Novel. But most don't know that since its appearance in 1851, it has been revised in substantial ways that alter its original meaning. Melville's masterpiece is described as a "fluid text": it exists in multiple versions, each revealing shifting intentions. The new Longman Critical Edition offers unprecedented access to the revisions that Melville made, the further changes and censoring imposed by his British editors, and controversial alterations made by modern scholars." "Bryant and Springer's introduction engages readers in the personal, social, and cultural context of Melville's novel, his life, and his writing process. To showcase the novel's "fluid text" features, a special typeface indicates hundreds of passages that were later revised, edited, and censored. On-page "Revision Narratives" explain the stories behind the major changes, and Explanatory Notes at the back of the book discuss literary allusions, as well as contemporary social, political, philosophical, and cultural references - some never before explained in any edition." "Concise footnotes and a modern Glossary bring obscure language and nautical terms to life, and diverse illustrations - including a new map of the Pequod's voyage, historical ship diagrams, relevant film stills, and comic-book art - depict whaling life and reveal how Melville's story is still being revised."--BOOK JACKET.

The Turner thesis: concerning the role of the frontier in American history (Problems in American civilization readings selected by the Dept. of American Studies Amherst College, 2,, 1949)
"THE TURNER THESIS: CONCERNING THE ROLE OF THE FRONTIER IN AMERICAN HISTORY is a series of critical essays on both sides of the debates regarding the settling of the western portion of the North American Continent. Essays include, "The Significance of the Frontier in American History," "Contributions of the West to American Democracy," "Sections-Or Classes?," Political Institutions and the Frontier," "The Frontier and American Institutions: A Criticism of the Turner Theory," "The American Frontier-Frontier of What?," "Frederick Jackson Turner," "The Frontier and the 400 Year Boom," "A Meaning for Turner's Frontier, Democracy in the Old Northwest," and "Frontier Democracy: Social Aspects.""-Print ed.

Amelia Earhart: Kansas girl (The Childhood of famous Americans, ,, 1950)
Description Not Provided

Sun in the sky (Civilization of the American Indian, 30,, 1950)
Description Not Provided

Josefina Learns a Lesson: A School Story (American girls collection. Josefina, 1824, 2, 1, 1997)
Josefina and her sisters distrust learning to read and write, as well as other changes their Tía Dolores is bringing to the household, because they fear they will lose their memories of their mother.

The Comanches: lords of the south plains (Civilization of the American Indian, ,, 1952)
Description Not Provided

Knute Rockne, young athlete (Childhood of famous Americans, ,, 1952)
A biography focusing on the childhood of the legendary football coach at Notre Dame, who won fame for his insistence on good sportsmanship and his football strategy.

Indian removal: the emigration of the Five Civilized Tribes of Indians (Civilization of the American Indian, 2,, 1976)
Description Not Provided
Choctaw removal --, The Treaty of Dancing Rabbit Creek --, Indians explore the Western country --, Chocktaw emigration begins --, Suffering of the emigrants --, Emigration resumed in 1832 --, Experiences on the march --, Condition of the immigrants --, Creek removal --, Efforts to remove Creek Indians from Alabama --, An Emigrating party in 1834 --, Frauds on the Creek Indians --, The Creek "War" of 1836 --, Wholesale removal of the Creeks by force --, A Journal of events --, Creek suffering- removal complete --, Chickasaw removal --, The Chickasaw treaty of Pontotoc --, Migration of the Chickasaw Indians --, Chickasaw settlements in the West --, Cherokee removal --, Oppression of the Cherokee Indians --, Cherokee Indians defend their tribal existence --, A Tragic migration --, The Schermerhorn "Treaty" - last stand of the Cherokee --, March of the broken spirited --, A Captive nation --, The Trail of tears --, Seminole removal --, The Seminole Indians --, The Second Seminole war --, The Fate of Holahte Emathla --, Hunting the Seminole Indians out of the swamps --, The Capture of Osceola --, Seminole captives deported --, The Surrender of Pascofa.

The undeclared war, 1940-1941 (Their The world crisis and American foreign policy, ,, 1953)
Description Not Provided